Biological activity of terminally gamma-ray-sterilized titanium and hydroxyapatite coated with a growth factor−apatite composite layer. (September 2020) - Yasunaga, Mayu; Kobayashi, Fumiko; Hara, Yuki; Yamazaki, Masashi; Ohno, Tadao; Ito, Atsuo
Graphical abstract: Highlights: Mitogenic activity of FGF-2−apatite remained unchanged with gamma ray irradiation. Irradiation still had impacts on the structural properties of original FGF-2. In the presence of dry ice, the impacts on molecular weight or epitope was reduced. FGF-2−apatite has radioprotective property on titanium and ceramic hydroxyapatite. Abstract: Implantable medical devices coated with fibroblast growth factor-2 (FGF-2) −apatite composite layers show enhanced soft-tissue formation, bone formation and angiogenesis owing to the biological activity of FGF-2. FGF-2−apatite composite layers faced the challenge of terminal sterilization. The purpose of the present study is to clarify the effects of the terminal gamma ray sterilization of titanium and ceramic hydroxyapatite coated with FGF-2−apatite composite layers on the biological activity of FGF-2 in vitro . The mitogenic activity of FGF-2 in FGF-2−apatite composite layers on titanium pins and ceramic hydroxyapatite remained unchanged with gamma ray irradiation at a dose of 25 kGy. In contrast, FGF-2 adsorbed on apatite, embedded in gelatin and pure FGF-2 without apatite in the aqueous state were highly susceptible to gamma ray irradiation. Despite the unchanged mitogenic activity, the FGF-2 in FGF-2−apatite composite layers still undergoes certain alterations. The first alteration is in the molecular weight or epitope of the original FGF-2, evidenced by the attenuation of the western blot main bands (17 and 34 kDa) and the appearance of over 63 kDa smeared bands. The second alteration is that leading to inactivation of the extracellular signal-regulated kinase1/2 (ERK1/2) phosphorylation pathway. The gamma-ray-irradiation-mediated attenuation of the 17 kDa band was recovered to 42% from 22% of unirradiated control when the FGF-2−apatite composite layers on titanium pins were gamma-ray-sterilized in the presence of dry ice. Our data suggest that apatite coprecipitated with FGF-2 on titanium and ceramic hydroxyapatite has a higher level of radioprotective property than apatite adsorbing FGF-2 or gelatin embedding FGF-2.